Urban Heat Management in Louisville, Kentucky: A Framework for Climate Adaptation Planning. (June 2023) - Stone, Brian; Lanza, Kevin; Mallen, Evan; Vargo, Jason; Russell, Armistead
We explore the potential for cities to develop urban heat management plans to moderate rising temperatures and to lessen the impact of extreme heat on human health. Specifically, we model the impacts of heat management strategies, including tree planting and other green infrastructure, cool roofing and paving, and a reduction in waste heat emissions from buildings and vehicles, on estimated heat-related mortality across Louisville, Kentucky. Our assessment finds a combination of urban heat management strategies to lessen summer temperatures by as much as 10°F on hot days and to reduce estimated heat-related mortality by more than 20 percent.